Outcome of Contemporary Nonsurgical Endodontic Retreatment: A Systematic Review of Randomized Controlled Trials and Cohort Studies - Mohammad Sabeti; Yunro Chung; Nasrin Aghamohammadi; Ava Khansari; Reza Pakzad; Amir Azarpazhooh (2024)
IntroductionThe success rates of NS-ReTx have varied across decades of prior research. Nonetheless, recent endodontic advances have substantially enhanced case management. This systematic review aimed to identify rigorous studies on contemporary NS-ReTx, investigating both periapical healing—evaluated strictly for complete resolution or loosely for size reduction of periapical radiolucency—and success, denoting clinical normalcy combined with periapical healing.MethodsWe systematically searched MEDLINE, Embase, Web of Science, the Cochrane Library, and gray literature from January 1988 to December 2022. Article selection and data extraction were independently conducted by three reviewers. Selected studies underwent risk of bias assessment, and evidence quality using the Grading of Recommendations, Assessment, Development, and Evaluation approach. Meta-analysis and meta-regression established pooled outcome rates, 95% confidence intervals (CI), and significant clinical prognostic factors (P <0.05).Results29 articles were included. Pooled periapical healing rates using strict and loose criteria were 78.8% (95% CI: 75.2-82.4) and 87.5% (95% CI: 83.8-91.2), respectively. Pooled success rates using strict and loose criteria were 78.0% (95% CI: 74.9-81.2) and 86.4% (95% CI: 82.6-90.1), respectively. Meta-regression analyses revealed significant influences on NS-ReTx outcomes (P <0.05), including periapical status, lesion size, apical root filling extent, and follow-up duration.ConclusionsContemporary NS-ReTx shows encouraging outcomes, achieving periapical healing and success rates ranging from approximately 78% (strict criteria) to 87% (loose criteria). The absence of or smaller preoperative lesions, adequate root filling length, and extended follow-ups significantly improve NS-ReTx outcomes. Integrating these factors into treatment planning is pivotal for optimizing the outcome of NS-ReTx.